Advanced technologies for next generation integrated circuits - Srivastava, Ashok (College teacher); Mohanty, Saraju P. (The Institution of Engineering and Technology, 2020)
Novel devices with the potential to provide alternatives to existing nanometer CMOS technology are the subject of research in the fields of electronic materials and electronic design automation. This book explores the materials and design requirements of emerging integrated circuit technologies, and outlines their prospective applications.
Keywords: Interconnects (Integrated circuit technology); elektronické knihy; electronic books